Interaction Process Between Humans and ChatGPT in the Context of Interpersonal Communication - Haqqu, Rizca; Rohmah, Salwa Nur (Universitas Telkom, 2024)
This study examines human interaction with artificial intelligence technology, focusing on the implementation of ChatGPT, a chatbot developed by OpenAI. Through the Human-Machine Communication (HMC) approach, the research describes human-like attributes in ChatGPT, exploring emotional responses and utility in educational, professional, and personal contexts. Qualitative research methods with triangulation techniques were used for a holistic understanding, involving interviews, observations, and document analysis. The results indicate that ChatGPT can provide adaptive responses, adjusting language style, and presenting information with self-awareness. Comparisons between human-to-human and human-to-machine interactions, particularly through ChatGPT, reveal significant differences. In human-to-human communication, the primary role is given to humans as message sources, while in machine communication, ChatGPT becomes an interactive partner, especially in text messages. Despite similarities in interpersonal communication features, such as feedback, personal relationship cues are more pronounced in human-to-human interactions. Factors like self-concept, openness, and confidence are dominant in human-to-human communication, while AI literacy becomes crucial in interactions with machines. Keywords: Human-Machine Communication, ChatGPT, Interaction, Interpersonal